2003
DOI: 10.1007/978-3-540-39867-7_15
|View full text |Cite
|
Sign up to set email alerts
|

MobileMAN: Mobile Metropolitan Ad Hoc Networks

Abstract: Abstract. MobileMAN is a project funded by the Future and Emerging Technologies arm of the IST Programme of the the European Commission. This project investigates the potentialities of the Mobile Ad hoc NETworks (MANET's) paradigm. Specifically, the project aims at defining and developing a metropolitan area, self-organizing, and totally wireless network, called Mobile Metropolitan Ad hoc Network (Mobile-MAN). The main technical output of this proposal can be summarized as follow. i) Development, validation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Either common APIs for "ad hoc programming" should be strictly followed or simulators should also provide execution environments allowing the simulation code to be directly executable on devices. Third, it is very likely that MANETs will be deployed within the metropolitan environment [23]. Project proposing constrained mobility models [56][67] [38] were a first step towards realistic models.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Either common APIs for "ad hoc programming" should be strictly followed or simulators should also provide execution environments allowing the simulation code to be directly executable on devices. Third, it is very likely that MANETs will be deployed within the metropolitan environment [23]. Project proposing constrained mobility models [56][67] [38] were a first step towards realistic models.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…In MobileMAN [12], information collected at different layers of the networking stack are shared in a common local memory structure and exploited to adapt the behavior of the node depending on the particular circumstance the node operates in. Such an approach satisfies the layer separation principle, i.e., protocols belonging to different layers can be added/removed from the protocol stack without modifying the protocols operating at the other layers.…”
Section: Related Workmentioning
confidence: 99%
“…In several recent works [8], [9], [10]; the authors point out the need of a cross-layering design. More than routing, research has shown that several mechanisms can profit by the knowledge of some parameters that are typically confined at the MAC: transport, power management, cooperation, etc……”
Section: Cross-layeringmentioning
confidence: 99%
“…Exportable parameters module: the architecture design foresees the access to MAC parameters for a full integration of mechanisms traditionally working at different layers. This is enabled by a cross-layering architecture as the one proposed for the MobileMAN project [10]. In this architecture the shared memory component acts as exchange area of networking information (parameters, status, etc…) for all the layers.…”
Section: Figmentioning
confidence: 99%